Integrated SQC and FMEA Framework for Woven Bag Defect Reduction In Manufacturing Industry: Kerangka Terpadu SQC dan FMEA untuk Pengurangan Cacat Woven Bag Di Industri Manufaktur - Asmaul Husna; Enny Aryanny (Academia Open, 2026)
General Background: In highly competitive manufacturing industries, systematic quality control is required to maintain product conformity and reduce defect rates. Specific Background: PT XYZ, a plastic packaging manufacturer, recorded woven bag production of 41,749,730 sheets in 2025 with a defect rate of 3.14%, exceeding the company target of below 2%, resulting in rework and recycled products. Knowledge Gap: Previous studies combining Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA) applied SQC tools to aggregated defect data without differentiating defect types, limiting analytical precision. Aims: This study aims to analyze woven bag quality using an integrated SQC and FMEA framework and to determine prioritized corrective actions based on Risk Priority Number (RPN). Results: Four dominant defects were identified: knit-through (354,623 sheets; 27.1%), improper stitching (25.6%), uneven cutting (24.3%), and printing mismatch (23%). Scatter diagrams indicated a positive relationship between production volume and defect quantity, while p control charts revealed multiple points outside control limits. FMEA results showed the highest RPN (336) for knit-through caused by suboptimal yarn tension on the circular loom machine. Novelty: This research applies SQC tools separately to each defect category, generating more detailed diagnostic insights prior to FMEA prioritization. Implications: The findings provide data-driven recommendations, including sensor upgrades on circular loom machines, routine cleaning of cutting tools, scheduled cliché replacement, and standardized machine settings to reduce woven bag defects and strengthen manufacturing quality control. Highlights: Knit-through recorded the largest proportion of nonconformities at 27.1% of total rejected output. Control chart evaluation showed several monthly proportions exceeding statistical limits. The highest priority corrective action targeted yarn tension deviation on the circular loom with an RPN of 336. Keywords: Statistical Quality Control, Failure Mode and Effect Analysis, Risk Priority Number, Woven Bag Defects, Manufacturing Quality Control